1996
DOI: 10.1007/bf00034074
|View full text |Cite
|
Sign up to set email alerts
|

Comments on mixed-mode fracture in adhesive joints

Abstract: We have employed the asymmetric double cantilever beam (ADCB) specimen, which consists of a brittle adhesive bonding aluminium-alloy substrates, to measure the toughness, G~. We have investigated whether the ratio of the heights of the specimen arms (i.e. defined by the parameter A, where A = hi/h2) has any significant effect on the value of G~. We find no significant effects, and compare our results to those previously reported where a dramatic effect was found, but could not be explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Knowing the geometry of the adherend and the load at a given crack length allowed the adhesive fracture energy, G c , of the bond to be measured [28]. With the specimen bonded to a stiff base the failure tended to propagate at, or very close to the aluminium/epoxy interface [29]. For the three-layer specimens a similar approach was used.…”
Section: Mechanical Testingmentioning
confidence: 99%
“…Knowing the geometry of the adherend and the load at a given crack length allowed the adhesive fracture energy, G c , of the bond to be measured [28]. With the specimen bonded to a stiff base the failure tended to propagate at, or very close to the aluminium/epoxy interface [29]. For the three-layer specimens a similar approach was used.…”
Section: Mechanical Testingmentioning
confidence: 99%
“…In the literature, numerous works have been directed on determining strength and fracture behavior of similar material sandwiched joint. These include investigations upon the effect of bond thickness [2][3][4] , crack path propagation [5][6][7] and assessment of fracture initiation criteria [8][9][10][11][12] . It has been reported that the strength and fracture behavior of the rubber modified adhesive joint is greatly dependent on the adhesive bond thickness and existence of cracks or flaws [2,3] .…”
Section: Introductionmentioning
confidence: 99%
“…The load was applied to the end of the specimen, and the load and crack length were measured. Knowing the geometry of the joint and the load at a given crack length allowed the adhesive fracture energy, G c , to be ascertained [28,29]. For both the twoand three-layer specimens the results were then displayed in a similar fashion to a 'C-scan', with a grey-level square representing the toughness at a given point on the specimen.…”
Section: Mechanical Testingmentioning
confidence: 99%
“…In the case of the two-layer specimens, each strip was bonded to a stiff aluminium-alloy base and an end block was glued to one end of the aluminium-alloy adherend. With the specimen bonded to the stiff base the failure would tend to propagate at, or very close to the aluminium-alloy/epoxy interface [29]. For the three-layer specimens a similar approach was used.…”
Section: Mechanical Testingmentioning
confidence: 99%